Between Qadar and Ikhtiar: Religious Interpretations of the Manangka Hujan Tradition in Padang Pariaman - David Khalik (Islamic Thought Review, 2025)
This study examines the Manangka Hujan tradition in Nagari Sikucua, Padang Pariaman Regency, which continues to be practiced within various customary and religious contexts. Commonly perceived as a rain-regulating ritual, this tradition raises theological questions concerning the relationship between human agency (ikhtiar), divine decree (qadar), and God’s absolute sovereignty. The study aims to analyze how local religious leaders interpret the concept of destiny as embedded in the Manangka Hujan tradition. Employing a qualitative research design, data were collected through in-depth interviews with religious leaders using a snowball sampling technique and analyzed through the interactive model proposed by Miles and Huberman. The findings reveal that religious leaders generally interpret Manangka Hujan not as an attempt to manipulate divine will, but as a form of human effort situated within the domain of qadar mu‘allaq, which allows for change through prayer, ethical intention, and reliance upon God (tawakkul). They maintain a clear distinction between qadar mubram, which is absolute and unchangeable, and qadar mu‘allaq, which is conditional and responsive to human endeavor. This study contributes to the discourse on contextual Islamic theology by illustrating how theological concepts of destiny are negotiated and rearticulated within local Islamic traditions, thereby enriching scholarly understandings of the dynamic relationship between religious doctrine and local wisdom in Minangkabau society.